2010
DOI: 10.1053/j.gastro.2010.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Gene Deficiency in Mice Impairs Host Resistance to an Enteric Parasitic Infection

Abstract: Background & AimsHyperplasia of mucin-secreting intestinal goblet cells accompanies a number of enteric infections, including infections by nematode parasites. Nevertheless, the precise role of mucins in host defense in nematode infection is not known. We investigated the role of the mucin (Muc2) in worm expulsion and host immunity in a model of nematode infection.MethodsResistant (BALB/c, C57BL/6), susceptible (AKR), and Muc2-deficient mouse strains were infected with the nematode, Trichuris muris, and worm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
193
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(212 citation statements)
references
References 48 publications
14
193
3
Order By: Relevance
“…171 In addition, the host can produce serine-protease inhibitors that prevent further loss of mucin 2. 171 Consistent with these data, Muc5ac is only upregulated in resistant mouse strains 170 and Muc5ac-deficient mice have impaired expulsion of T. muris, N. brasiliensis, and T. spiralis. 173 Increased mucus production and the mucin switch are largely driven by IL-13, 173 IL-4, 174 and IL-22, 175 but the principle of physical obstruction provided by mucus layers can also be extended to other mucosal sites such as the lungs where the lectin surfactant protein-D, which acts as a lubricant, is needed for optimal protection against the pulmonary stage of N. brasiliensis infection.…”
Section: Expulsionmentioning
confidence: 53%
See 1 more Smart Citation
“…171 In addition, the host can produce serine-protease inhibitors that prevent further loss of mucin 2. 171 Consistent with these data, Muc5ac is only upregulated in resistant mouse strains 170 and Muc5ac-deficient mice have impaired expulsion of T. muris, N. brasiliensis, and T. spiralis. 173 Increased mucus production and the mucin switch are largely driven by IL-13, 173 IL-4, 174 and IL-22, 175 but the principle of physical obstruction provided by mucus layers can also be extended to other mucosal sites such as the lungs where the lectin surfactant protein-D, which acts as a lubricant, is needed for optimal protection against the pulmonary stage of N. brasiliensis infection.…”
Section: Expulsionmentioning
confidence: 53%
“…Ejection of gastrointestinal nematodes relies on a combination of physiological mechanisms that include enhanced mucus secretion by goblet cells, release of neutralizing proteins by granulocytes and epithelial cells, epithelial hyperproliferation, and increased intestinal peristalsis (Figure 1c), perhaps the most important of which is augmented production of mucins. Mucins trap worms by impeding motility, and hence mice lacking mucin 2 (the predominant glycoprotein of the mucus layer) are rendered susceptible to T. muris infection and show delayed worm expulsion, 170 illustrating the importance of this barrier. Nonetheless, T. muris and other nematode larvae are still able to penetrate the mucus layer of mucin-proficient mice upon infection, indicating that they have evolved strategies to circumvent this barrier.…”
Section: Expulsionmentioning
confidence: 99%
“…Muc1-deficient mice are less resistant to Helicobacter pylori colonization than control littermates and develop a severe subsequent gastritis (41). Muc2-deficient mice spontaneously develop colitis (35) and have impaired resistance against enteric infection (42).…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of MUC2 can be influenced by a broad range of mediators including cytokine signals, microbial‐derived products, adrenocorticotropic hormones, autophagic proteins, reactive oxygen species and components of the inflammasome (NOD‐, LRR‐ and pyrin domain‐containing 6) 10, 11, 42, 43, 44, 45, 46…”
Section: Muc2 Biosynthesismentioning
confidence: 99%
“…Indeed, subsequent characterization of animal models for GI helminth infections and the development of protocols to assess mucosal barrier properties have allowed the development of robust systems to directly investigate aspects of mucus barrier function and properties in vivo. These studies have demonstrated that mucins and mucus‐associated proteins hold key roles in altering the intestinal niche to enhance parasite expulsion, thus contributing to immune‐mediated host protection 9, 10, 11. Further insight into the precise functional role(s) that mucins and mucus‐associated proteins play within the mucus barrier may uncover potential avenues for novel therapeutic targets to eradicate this group of important neglected tropical diseases.…”
Section: Introductionmentioning
confidence: 99%